Phosphine-catalyzed dearomative [3+2] annulation of 3-nitroindoles and allenoates. Issue 29 (18th July 2019) - Liu, Kui; Wang, Gang; Cheng, Shao-Jie; Jiang, Wen-Feng; He, Cheng; Ye, Zhi-Shi
Graphical abstract: Highlights: An efficient phosphine-catalyzed dearomative [3+2] annulation of 3-nitroindoles with allenoates was developed. This strategy features mild reaction conditions, high functional group tolerance, and scalability. The moderate enantioselectivity was obtained in the presence of chiral Trost's phosphine catalyst. Abstract: The efficient phosphine-catalyzed dearomative [3+2] annulation of 3-nitroindoles with allenoates has been successfully developed, providing a facile access to cyclopenta[ b ]indolines with good to excellent yields and high diastereoselectivities. This strategy features mild reaction conditions, high functional group tolerance, and scalability. Additionally, the 2-nitrobenzofuran and 2-nitrobenzothiophene were good dearomative [3+2] annulation partners.